KEPUASAN MASYARAKAT TERHADAP PUBLIC SERVICE HALL DI KABUPATEN PAMEKASAN - Musoffan Musoffan; Darwis Darwis; Ahmad Rajaul Masrur (Politeknik Ubaya, 2019)
This study to assess community satisfaction with the public service hall in Pamekasan district as a breakthrough from the performance of the Pamekasan Regency Government.Retrieving data in this study by distributing questionnaires to the public using the Slovin Analysis formula used in this study, namely by using the public satisfaction index. The results of this study indicate that the Pamekasan Community Satisfaction Index towards Service Hall Public is 81,141 and based on the decision of the Minister of State Apparatus Number KEP / 25 / M.PAN / 2004 the value of the IKM is in the conversion interval value 62,51 - 81,25 with the predicate Good . The Public Service Hall in Pamekasan Regency was the first program in Madura and became the first breakthrough in Pamekasan Regency so that it received a certificate from the World-Indonesia Record Museum (MURI) category as the fastest district in establishing a Public Service Mall, this is nothing but the achievement of the District’s vision and mission Pamekasan headed to “Pamekasan Hebat“ which was Bhejjreh, Rajjheh and Parjhugeh.